The Students’ Vocabulary Learning Strategies and Vocabulary Size of the English Study Program of UIN Fatmawati Soekarno Bengkulu - Mefi Yulianti; Alamsyah Harahap; Ira Maisarah (English Education Study Program Faculty of Teacher Training and Education, 2023)
The objectives of this research are to analyze information about students' vocabulary learning strategies and vocabulary size. This research is mixt-methods; there were descriptive quantitative and qualitative method. The sample of this research is students’ English Study Program of UIN Fatmawati Bengkulu. The data were gathered by using questionnaires, test and interview, and were analyzed by descriptive quantitative and qualitative analysis.The results showed that there was no difference which is significant in terms of frequency of using among each student of English education at UIN FAS Bengkulu. So the dominant strategies were used by students that were determination strategies (M=3.3), metacognitive strategies and memory strategies (M=3,2), cognitive strategies (M=3.1), and the last social strategies (M=3). It meant that determination strategies most frequency used by the students English Study Program of UIN FAS Bengkulu. Result for students’ vocabulary size showed that average vocabulary sizes below 8000 word families. Meanwhile from interview data, the students used metacognitive, memory, determination and social strategies for their vocabulary learning. In conclusion, each strategy is a good vocabulary learning strategies to students for improving vocabulary size andmay help lecturers and students to facilitate English vocabulary learning by English Study Program students and other students.